Pengaruh Pengawasan Terhadap Implementasi Kebijakan Izin Mendirikan Bangunan Di Kabupaten Deliserdang - Monang Sitorus (Jurnal Wacana Kinerja, 2020)
The aim of this research is to analyze the inﬂuence controlling towards policy implementation building ooniruction permission (Case studyofRegency Deli Serdang). Thetheory ofoontrolling tested out by the writerbyRobbins and Coulter (2006) wich consists of three dimension namely (1). standars, (2). measurements and comparison (3) action. The theory performance tested out by the writer by Iones (1994:166) dimension (1). organization (2). interpretation (3). aﬂication. 'D1ese three dimension were applied by the to analysis policy implementation building amtruction permission in Regency Deliserdang. To inden tify the three inﬂuenceof dimension, a survey approach was conducted through a proportional sample of 130 head of household (informants). The data were analyzed by using Path Analysis, in the program SPSS. The value was found out eadi dimensions as follows; (a). inﬂuence standars ( X) to policy implementation building contruction permission (Y) is 26.53% (low category), inﬂuense measurements and comparison (X) topolicy implementation building contruction permission (Y) is 16.19% (low category), inﬂuense action (X) topolicy implementation building contruction permission (Y) is 33.86% (medium category). Theeﬁizct ( X,,X,,X,) to Y is 76.58% (strong category, and the residu is 23.42% inﬂuenced theother dissimilar factor (epsilon).